2011
DOI: 10.1068/p7021
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Perceptual Structure of Rectangles through Goodness-of-Fit Ratings

Abstract: Three experiments were carried out to investigate the internal structure of a rectangular frame to test Arnheim's (1974 Art and Visual Perception, 1988 The Power of the Center) proposals about its 'structural skeleton'. Observers made subjective ratings of how well a small probe circle fit within a rectangle at different interior positions. In experiment 1, ratings of 77 locations were highest in the center, decreased with distance from the center, greatly elevated along vertical and horizontal symmetry axes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…1 Arnheim (1974) speculated that a frame has a "structural skeleton" defined by dynamic forces propagated from its sides. Recent empirical measurements have supported Arnheim's intuitions remarkably well (Palmer 1991, Palmer & Griscom 2012, Palmer & Guidi 2011. When observers rated the "goodness of fit" for the placement of a single probe circle at 35 locations within a rectangular frame, the center of the frame always had the highest average goodness rating, which decreased monotonically with distance from the center.…”
Section: The Structure Of a Rectangular Framementioning
confidence: 69%
“…1 Arnheim (1974) speculated that a frame has a "structural skeleton" defined by dynamic forces propagated from its sides. Recent empirical measurements have supported Arnheim's intuitions remarkably well (Palmer 1991, Palmer & Griscom 2012, Palmer & Guidi 2011. When observers rated the "goodness of fit" for the placement of a single probe circle at 35 locations within a rectangular frame, the center of the frame always had the highest average goodness rating, which decreased monotonically with distance from the center.…”
Section: The Structure Of a Rectangular Framementioning
confidence: 69%
“…2c-d (Firestone & Scholl, 2014; see also Psotka, 1978). And, beyond documenting their existence, other work has suggested that such skeletal representations might also influence certain types of higher-level subjective judgmentssuch as how aesthetically pleasing a shape (or even a realworld structure such as a rock garden) is (Palmer & Guidi, 2011;van Tonder, Lyons, & Ejima, 2002), or what that shape should be called (Wilder, Feldman, & Singh, 2011).…”
Section: Shape Skeletonsmentioning
confidence: 99%
“…The dot patterns were chosen to represent each symmetry subgroup for this class of images (Palmer, 1991). The circle-in-a-frame images (Palmer & Guidi, 2011) consisted of 35 images of a single black dot (20-pixel diameter) viewed in a white, horizontal, rectangular frame (200 × 300 pixels) with a 5-pixel black border. In each image, the dot appeared in one of 35 different positions arranged as a 5 × 7 grid, with 50 pixels between each position vertically and horizontally.…”
Section: Stimulimentioning
confidence: 99%